PROCESSING AND PACKAGING TECHNOLOGY APPLICATIONS TO EXTEND THE STORAGE IN THE TRADITIONAL HERBAL INDUSTRY - Milana, Lia; Juliar, Eka (Universitas Majalengka, 2022)
During a pandemic like today, a very strong immune system is needed to maintain the body's resistance so that it is not easily exposed to disease. Strong immune power is produced from foods and beverages that contain good nutrition and nutrition for the health of the body. One of the drinks that can increase the body's immune power is Traditional Jamu which is well known to the Indonesian people, because Indonesia is very famous for its rich herbal ingredients that have many health benefits. There are so many kinds of herbs that can be found in our country that many foreigners even hunt, because the properties contained in herbs are needed for body health and are rarely found in other countries. This is an advantage for us Indonesian people, who clearly will have no trouble getting raw materials to mix herbal drinks. This is an opportunity for our society, so that they can develop traditional herbal drinks to be more modern and penetrate the global market. This of course requires touches of renewable technology, so it is hoped that traditional Indonesian herbal drinks can be marketed to the wider community and the biggest hope is to enter the international market. However, in reality, there are several obstacles faced by traditional herbal drink manufacturers. Among them is the resulting product has a short shelf life. For this reason, it is necessary to transfer the right processing and packaging technology so that the product shelf life is longer. The method used in this research is a touch of transfer of processing technology and packaging technology to extend the shelf life of the traditional herbal medicine industry in Majalengka, so as to improve product performance.